IMPROVING STUDENTS’ WRITING NARRATIVE THROUGH WRITING GAMES FOR ACCELERATION CLASS - Kheryadi Kheryadi (Universitas Islam Sultan Agung, 2017)
This study addresses how writing games improve acceleration students’ writing narrative achievement, also observe how students’ behavior during playing the games and also the teacher on conducting the games along the research. This study has been conducted in acceleration students. It uses classroom action research, the data analyzed from qualitative and quantitative data. The qualitative data are about teacher’s interview and students’ questionnaire, while the quantitative data is about their scores on writing narrative. To solve the problem, the teacher has implemented Writing Games as a technique. Writing Games contain of games which tend to writing ability and in this case, the teacher chose two kinds of writing games; they are “Silly Story” and “What’s Next?”. “Silly Story” focuses on students’ ability on writing sentences and “What’s Next?” focuses on students’ ability on making paragraph. This research consists of two cycles and each of it has planning, action, observation and reflection. These findings implicate that acceleration students were interested with writing games and involved in it well. However, during the research, especially in the first cycle, there was still one group was less active in “Silly Story” because they could not discuss each other and the group was quiet big.